1998
DOI: 10.1038/sj.leu.2401129
|View full text |Cite
|
Sign up to set email alerts
|

Relation between age, immunophenotype and in vitro drug resistance in 395 children with acute lymphoblastic leukemia–implications for treatment of infants

Abstract: The prognosis of infant ALL, characterized by a high incidence of the immature CD10 negative B-lineage ALL (proB ALL) is poor. This study aimed to determine the resistance profile of infant ALL cells. In vitro drug resistance was determined by the MTT assay of 395 children with ALL at initial diagnosis: there were 21 infants Ͻ Ͻ Ͻ1.5 years of which nine Ͻ Ͻ Ͻ1 year, 284 children aged 1.5-10 years (intermediate age group) and 90 children Ͼ Ͼ Ͼ10 years. Immunophenotyping resulted in 310 cALL/preB ALL, 69 T-ALL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
139
2
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(156 citation statements)
references
References 18 publications
11
139
2
4
Order By: Relevance
“…These observations are consistent with previous reports of the in vitro cytotoxicity of these agents (Adamson et al, 1994;Klumper et al, 1995;Pieters et al, 1998;Kaspers et al, 2005). No significant differences in cytotoxicity were observed between DEX and MPRED (P40.05).…”
Section: Cell Line Drug Resistance Profilessupporting
confidence: 93%
See 1 more Smart Citation
“…These observations are consistent with previous reports of the in vitro cytotoxicity of these agents (Adamson et al, 1994;Klumper et al, 1995;Pieters et al, 1998;Kaspers et al, 2005). No significant differences in cytotoxicity were observed between DEX and MPRED (P40.05).…”
Section: Cell Line Drug Resistance Profilessupporting
confidence: 93%
“…This is true not only for relapsed ALL (Klumper et al, 1995) where in vivo selection of resistant clones occurs during therapy, but also in those newly diagnosed with the disease (Kaspers et al, 1997;Pieters et al, 1998). Much of our knowledge of the resistance phenotypes in ALL has been derived using isolated bone marrow specimens studied in short-term culture using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay.…”
mentioning
confidence: 99%
“…So poor and intermediate responders were in vitro 25-fold more resistant to L-asparaginase (P ¼ 0.02) than children with a good in vivo response ( Figure 2). In concordance with earlier studies, 34 T-ALL cells were significantly more in vitro resistant to L-asparaginase than precursor B-ALL cells (LC 50 median 1.22 IU/ml versus 0.10 IU/ ml; Po0.001). Only one 8-year-old girl with T-ALL and an initial WBC of 132 Â 10 9 per liter had a poor clinical response (WBC 25 Â 10 9 per liter at day 0, absolute leukemic cell count 19.3 Â 10 9 per liter), whereas her blasts were in vitro sensitive to L-asparaginase.…”
Section: Clinical Responsesupporting
confidence: 91%
“…This is in concordance with the fact that T-ALL cells were found to be in vitro more resistant to L-asparaginase. 34 For BCRABL/t(9;22), the in vivo resistance to L-asparaginase is a new finding. In the present study we also showed that in vitro resistance to L-asparaginase is related to the clinical response to PEG-asparaginase as single drug.…”
Section: Clinical Responsementioning
confidence: 99%
“…Prednisolone (the biologically active metabolite of prednisone) dosages needed to eliminate 50% of infant ALL cells in vitro typically are B500 --fold higher than the dosages required to eradicate similar amounts of precursor B-ALL cells from children older than one year of age (that is, non-infants). 4 Moreover, approximately 30% of infants with MLL-rearranged ALL show a poor prednisone response in vivo, compared with only B10% of non-infant pediatric precursor B-ALL cases. 5 As the in vitro prednisolone response and the prednisone response in vivo represent important prognostic factors, 6 --8 the poor prognosis for MLL-rearranged infant ALL seems to a large extent associated with glucocorticoid resistance.…”
Section: Introductionmentioning
confidence: 99%